Assessment of Drug Usage Pattern in Patients Treated for Vernal Keratoconjunctivitis Attending a Tertiary Eye Care Centre in Eastern India: A Cross-Sectional Study - Maitra, Aditi; Bhattacharyya, Shashwat; Biswas, Arunava; Samanta, Swapan Kumar; Mukherjee, Shatavisha; Era, Nikhil (Nepalese Journal of Ophthalmology, 2018)
Introduction: Vernal keratoconunctivitis is a recurrent, seasonal, allergic condition affecting children and adolescents in warmer regions worldwide. Objective: To assess the drug usage pattern for the management of vernal keratoconjunctivitis (VKC). Materials & Methods: This was a 12 weeks long hospital based cross sectional study conducted in the outpatient unit of the department of ophthalmology of a teaching hospital. It included all consecutive patients diagnosed with VKC who satisfied the inclusion criteria. Patients underwent clinical examination and the severity of their disease was graded. Their prescriptions were scanned for duration of therapy, total number of medications, route of administration, the frequency of dosage and change in medications if any, generic names of drugs being prescribed or not and all demographic parameters were recorded in a suitable record form. A p value of <0.05 was considered to be statistically significant. Results: 248 patients were enrolled in this study of whom the majority were male (172). The average age of the patients was 8.27 years (SD ± 3.02 years). The mean duration of disease was 15 months (SD ± 9.13 years). The greatest number of children belonged to severity grade 1 (27.82%). The total number of drugs prescribed in this study was 583 with an average of 2.26 drugs per encounter. The commonest prescribed drugs were topical anti-allergics (26.75%) followed closely by lubricants (25.73%) and topical steroids (21.42%). Conclusion: Anti allergics and lubricants are the mainstays in the management of VKC. The current study is reflective of this. Clearer guidelines need to be formulated for the better and rational management of VKC.